2019
DOI: 10.1108/ijphm-07-2018-0036
|View full text |Cite
|
Sign up to set email alerts
|

Influence of service quality and corporate image on the satisfaction of patients with Brazil’s National Cancer Institute

Abstract: Purpose The purpose of this paper is to better understand the influence of service quality and corporate image of Brazil’s National Cancer Institute (INCA) on the satisfaction of its outpatients. Design/methodology/approach The study is quantitative, with data collected from a self-administered structured questionnaire answered by a sample of 434 outpatients of Hospital do Câncer I, the largest and oldest hospital operated by the INCA. The data were treated with covariance-based structural equation modeling.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 52 publications
2
16
0
Order By: Relevance
“…In the context of retailing, it is evident in the literature that store image (from store attributes perspective) has long been used as an antecedent of service quality (see Bao et al, 2011;Konuk, 2018). Whereas, in different research settings, the construct "corporate image" has appeared as a consequence of service quality (Coutinho et al, 2019;Darmawan et al, 2018;Giovanis & Tsoukatos, 2017;Hassan et al, 2019). But in the platform of retailing, study addressing the CI construct (from holistic viewpoint) as an outcome variable of service quality is still scant (Nesset et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of retailing, it is evident in the literature that store image (from store attributes perspective) has long been used as an antecedent of service quality (see Bao et al, 2011;Konuk, 2018). Whereas, in different research settings, the construct "corporate image" has appeared as a consequence of service quality (Coutinho et al, 2019;Darmawan et al, 2018;Giovanis & Tsoukatos, 2017;Hassan et al, 2019). But in the platform of retailing, study addressing the CI construct (from holistic viewpoint) as an outcome variable of service quality is still scant (Nesset et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that the quality perceived by service customers directly and positively impacts their satisfaction (Prakash and Srivastava, 2019;Anabila et al, 2019;Souki et al, 2020;Miranda et al, 2018;Swain and Kar, 2018;Ahmed et al, 2019;Kant and Jaiswal, 2017;Yu et al, 2014). Likewise, investigations in the health-care field (Perera and Dabney, 2020;Coutinho et al, 2019;Giovanis et al, 2018;Batbaatar et al, 2017; and, more particularly, in dentistry (Luo et al, 2018;Bahadori et al, 2015; and in orthodontics Lyros et al, 2019;Wong et al, 2018;Pacheco-Pereira et al, 2018;Al Balushi et al, 2017;Shahrani et al, 2015;Khan et al, 2014), corroborate this finding. Finally, the perceived quality also impacts patients' attitudes and behavioural intentions (Anabila et al, 2019;Souki et al, 2020;Yu et al, 2014), making their monitoring even more pivotal to health professionals.…”
Section: Literature Review On Perceived Quality and Patients' Satisfa...mentioning
confidence: 82%
“…Public satisfaction can be measured by a number of indicators, namely reliability, responsiveness (Kant & Jaiswal, 2017), empathy (Ratnawati et al, 2020), professionalism, information availability, staff attitude, (Lanin & Hermanto, 2019), image (Coutinho et al, 2019). The satisfaction of street vendors relocation in the city of Yogyakarta is basically influenced by the culture of the city government of Yogyakarta.…”
Section: Resultsmentioning
confidence: 99%